The Relationship Between Customer Satisfaction and Organizational Success: A Study of Panasonic - Wanneyda Suvanmanee; Daisy Mui Hung Kee; Zhi Wei Lee; Chia Miin Low; Muhamad Amir Zakwan; Ankit Gupta; Rudresh Pandey; Fay Fahad Alfahad; Majdi Anwar Quttainah (Journal of the Community Development in Asia (JCDA), 2020)
The purpose of this study is to examine the customers' satisfaction that drives to the success of the company. There is a high competition between the brand of the electrical appliance, therefore customer satisfaction is one of the key elements to the success of the company. The study used a quantitative method which is a questionnaire to collect the data from respondents. It will enhance the understanding and importance of customer satisfaction toward a company able to lead to company success. The findings indicated that customer satisfaction is an important prediction of the success of the company.